Development and characterization of mouse monoclonal antibodies to eight human complement components: Analysis of reactivity with orthologs of nine mammalian genera. (February 2019) - Monedero, Marta; Infantes-Lorenzo, José A.; Moreno, Inmaculada; Martín, Ana Belén; Macias, Rocio I.R.; Toraño, Alfredo; Domínguez, Mercedes
Highlights: Mouse mAb to five human complement components (C1q, C4, C5, C9 and properdin) and three factors (H, B and D) haven been generated. Their reactivity to their orthologues of nine mammal genera have been determinated. These interspecies crossreactive antibodies can used valuable for the study of infection mechanisms in non-human mammals. These mAb can used to develop immunoassays for monitoring mammalian complement in normal and pathological conditions. Abstract: To study complement function in mammalian leishmanioses, we developed mouse monoclonal antibodies to the human complement system components C1q, C4, factor D, factor H, factor B, properdin, C5 and C9. Antibody specificity was determined by indirect and capture ELISA and by Western blot. In flow cytometry analysis, seven antibodies recognized the cognate component on human serum-opsonized Leishmania promastigotes. Antibody reactivity was screened against promastigotes opsonized with sera of nine mammalian genera: pig, guinea pig, goat, rabbit, cat, dog, hamster, jird and rat. No antibody recognized jird epitopes on promastigotes. Anti-C4, -properdin, and -C5b reacted with the orthologous protein of all other mammals tested except cat (anti-properdin) and hamster (anti-C5b); anti-C9 only recognized the rabbit ortholog, and anti-C1q, -factor B and -factor H did not react with any of the nine orthologs. Such interspecies crossreactive antibodies can be valuable tools for analysis of mammalian complement function in infectious diseases.